1998
DOI: 10.1046/j.1440-1797.1998.d01-28.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro suppression of parathyroid hormone secretion by 22‐oxa‐calcitriol in human parathyroid hyperplasia due to uraermia

Abstract: SUMMARY: 22‐oxa‐calcitriol (OCT), a vitamin D analogue, suppresses parathyroid hormone (PTH) secretion and has less calcaemic activity than 1,25‐dihydroxyvitamin D3 [1,25(OH)2D3] in vivo. In this study, we evaluated the effect of OCT on PTH secretion in vitro using human hyperplastic parathyroid tissue obtained during surgery for advanced renal hyperparathyroidism and normal bovine parathyroid glands to compare the effects of 1,25(OH)2D3. 22‐oxa‐calcitriol suppressed PTH secretion by nodular hyperplastic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(3 reference statements)
2
2
0
Order By: Relevance
“…Next, the mechanisms underlying the suppression of parathyroid function by PMIT were studied. As one of the mechanisms, OCT was shown to suppress the synthesis and secretion of PTH, as proven by the reduction in the PTH mRNA level [7,8,13]. The in vivo effect of the suppression of PTH synthesis and secretion by PMIT was observed in this study (Figs.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Next, the mechanisms underlying the suppression of parathyroid function by PMIT were studied. As one of the mechanisms, OCT was shown to suppress the synthesis and secretion of PTH, as proven by the reduction in the PTH mRNA level [7,8,13]. The in vivo effect of the suppression of PTH synthesis and secretion by PMIT was observed in this study (Figs.…”
Section: Discussionsupporting
confidence: 65%
“…Maxacalcitol (22-oxacalcitriol; OCT) is an analog of 1,25-dihydroxy vitamin D 3 (1,25-D 3 ) and has been shown to strongly suppress parathyroid function dose dependently and to improve bone disorder caused by SHPT in chronic dialysis patients [5,6]. Experimentally, it has been proved that OCT suppresses PTH mRNA expression in uremic rats without causing hypercalcemia and prevents the decrease in the vitamin D receptor (VDR) expression level in parathyroid gland as well as that of 1,25-D 3 [7][8][9]. Thus, we developed a direct percutaneous injection therapy of maxacalcitol (PMIT) into parathyroid glands.…”
mentioning
confidence: 99%
“…From the final PD parameter estimates (▶ Table 3), the estimated EC 50 of iPTH and cCa was 1.06 × 10 − 4 and 1.83 × 10 − 3 pg/mL, respectively (▶ Table 3). These estimate values are quite low, but they are similar to the effective concentration of maxacalcitol in in vitro pharmacology studies [13].…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, maxacalcitol is an analog of 1,25-dihydroxyvitamin D 3 (1,25-D 3 ) and has been shown to suppress parathyroid function dose-dependently and to improve bone disorder caused by SHPT in chronic dialysis patients [10,11,12,13]. Experimental studies have confirmed that maxacalcitol suppresses PTH mRNA expression in uremic rats without causing hypercalcemia and prevents the decrease in the expression level of vitamin D receptor (VDR) in parathyroid gland as well as that of 1,25-D 3 [14,15,16]. Although maxacalcitol has been recently developed as a new vitamin D 3 and its efficacy is anticipated in SHPT [13, 17, 18], there have been few reports on the usefulness of combination therapy of intravenous maxacalcitol and selective PEIT.…”
Section: Introductionmentioning
confidence: 99%